Exploring the Stages of Project-Based Learning for Enhancing Speaking Skill in Indonesian EFL Classroom - Ahsan Muzri. S; La Sunra (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The objective of this research is to know the stages of project-based learning in Indonesian EFL classroom in order to enhance students’ speaking skill. This study used experimental design. The sample of this study was twelfth grade students of SMAN 2 Sidenreng Rappang in academic year 20023/2024. The researcher used random sampling technique to get the sample, the students of XII MIPA 6 was selected to be the sample of the research. The researcher used speaking test which conducted in pretest and posttest as research instrument to know the progress of students’ speaking skill after implementing project-based learning in the treatment. The research results show that there are seven stages of project based learning which the researcher implemented in this research such as: The formulation of expected learning outcomes, Understanding the concept of teaching material, Skills training, Designing the project theme, Making the project proposal, Executing the project task, and Presentation of the project report. In implementing project-based learning in teaching speaking in Indonesian EFL classroom has significantly enhanced students’ speaking skill. The results demonstrated that the students' mean score increased from 15.88 in the pre-test to 18.81 in the post-test, indicating an improvement. This reflects 18.5% enhancement in the students' speaking performance from pre-test to post-test.